General Election 15th: Analysis the Tendency of Voters at Peninsular Malaysia (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
This research purposely has been done to determine the tendency of voters of the 15th General Election at Peninsular Malaysia. The characteristics of voters analyze in this research included the early voters, voters aged 18-20 years old, the total number of voters at each parliamentary seats, races and average gross income of the voters. However, this research has only taken into consideration the parliamentary seats won by Perikatan Nasional (PN) and Pakatan Harapan (PH) as the biggest coalition won the seats at Peninsular Malaysia. The analysis is dependent to the data from government agencies’ website which are Suruhanjaya Pilihan Raya Malaysia (SPR) and Department of Statistics Malaysia Committee (DOSM). The data has been analyze using SPSS Statistical Software (SPSS) by computing the significance level and the relationship between the chosen Member of Parliaments and the characteristics of the voters. From this research, the parliamentary seats won by each coalition is significantly influenced by all characteristics mentioned above except the percentage of early voters. This research is important as the 15th General Election shows an unexpected political situation which no coalition can simply form a government. It then led to the unstable political environment which also impact the performance of the country. Hence, the analysis of the voters’ characteristics is important to discover what is the reason led to the result of the election.